microRNA-494 Favors HO-1 Expression in Neuroblastoma Cells Exposed to Oxidative Stress in a Bach1-Independent Way - Piras, Sabrina; Furfaro, Anna L.; Caggiano, Rocco; Brondolo, Lorenzo; Garibaldi, Silvano; Ivaldo, Caterina; Marinari, Umberto M.; Pronzato, Maria A.; Faraonio, Raffaella; Nitti, Mariapaola (Frontiers in Oncology, 2018)
Heme oxygenase 1 (HO-1) is crucially involved in cell adaptation to oxidative stress and has been demonstrated to play an important role in cancer progression and resistance to therapies. We recently highlighted that undifferentiated neuroblastoma (NB) cells are prone to counteract oxidative stress through the induction of HO-1. Conversely, differentiated NB cells were more sensitive to oxidative stress since HO-1 was scarcely up-regulated. In the present work, we investigated the role played by miR-494, which has been proved to be involved in cancer biology and in the modulation of oxidative stress, in the up-regulation of HO-1. We showed that NB differentiation down-regulates miR-494 level. In addition, endogenous miR-494 inhibition in undifferentiated cells impairs HO-1 induction in response to exposure to 500µM H2O2, reducing the number of viable cells. The analysis of Bach1expression did not reveal any significant modifications in any experimental conditions tested, proving that the impairment of HO-1 induction observed in cells treated with miR-494 inhibitor and exposed to H2O2 is independent from Bach1. Our results underline the role played by miR-494 in favoring HO-1 induction and cell adaptation to oxidative stress and contribute to the discovery of new potential pharmacological targets to improve anticancer therapies.